A Rare Case Report of Unusual Path of Left Internal Jugular Central Line - Rajashekar Rangappa Mudaraddi; Hany Fawzi Greiss; Navin Kumar Manickam (Dubai Medical Journal)
Central venous cannulation is the most common procedure performed in perioperative setting and intensive care unit. Many case reports reported unusual positioning of central line catheters. Here, we would like to report a case of central line path in persistent left superior vena cava, a rare entity with a course similar to the right internal jugular central line. Preoperative computed tomography chest showed duplex superior vena cava which was not reported.